Patterns of Osteoporosis Treatment Initiation Following Low‐Trauma Fracture: A Population‐Based Retrospective Cohort Study in New South Wales, Australia, Using Linked Administrative Health Data - Mike Lin; Huy Nguyen; Thach Tran; Robert D. Blank; Dana Bliuc; Jacqueline R. Center (Medical Journal of Australia, 2026)
ABSTRACT Objectives To characterise osteoporosis medicine prescribing patterns following low‐trauma fractures and identify predictors of early treatment initiation. Study Type Retrospective population‐based cohort study. Setting New South Wales, Australia, using statewide linked administrative health data. Participants Adults aged ≥ 50 years with an incident low‐trauma fracture between January 2011 and June 2019. Main Outcome Measures Primary outcomes were osteoporosis treatment prescribing patterns and timing of initiation after incident fracture over 3 years, categorised as early (within 12 months), late (within 1–3 years) or no initiation. Secondary analyses examined predictors of time to treatment initiation within 12 months using Fine–Gray competing‐risk regression. Results Among 132,268 individuals with incident fractures, 63.7% (84,222) were female. Overall, 29,802 (22.5%) initiated osteoporosis medicine, whereas 102,466 (77.5%) remained untreated. Among females (mean [standard deviation] age, 77.7 [10.1] years), 20.1% initiated therapy within 12 months, 7.0% within 1–3 years, and 72.9% remained untreated. Among males (mean [standard deviation] age, 77.2 [10.0] years), the corresponding proportions were 10.8%, 3.7% and 85.6%. After accounting for the competing risk of death, treatment initiation was more likely with non‐distal fractures, older age, polypharmacy, prior steroid use, prior dual‐energy x‐ray absorptiometry and later fracture year, and less likely with greater comorbidity, rural or regional residence and prior hospitalisation for falls. The strongest associations were for hip or vertebral fracture (subdistribution hazard ratio range, 1.90–3.03) and high comorbidity burden (subdistribution hazard ratio range, 0.72–0.75). Almost one in four late initiators had a refracture before starting treatment. Denosumab rapidly replaced oral bisphosphonates as the dominant therapy over time. Conclusion More than three‐quarters of individuals remain untreated after fracture, highlighting persistent and substantial gaps in secondary fracture prevention. Treatment initiation is strongly associated with fracture site and multimorbidity burden, and initiation rates are lower in males. Increasing reliance on denosumab underscores the need for careful long‐term treatment planning and strategies.